Comparison of sweet potato starch extraction systems in Vietnam - Nguyen Duy Duc; Ilangantileke, S.G.; Wheatley, C.; Athapol Noomhorm; Jindal, Vinod Kumar; Vincent, Jean-Claude; Republic of Korea (Bangkok : Asian Institute of Technology, 1994)
Two winter season sweet potato varieties "Hoang long" and "Tu nhien", were selected for starch extraction. The composition of each variety such as starch content, dry matter, total sugar, total fibre and total ash content at two periods of 10 and 50 days ·after harvest were determined. The whiteness of starch extracted from peeled and unpeeled sweet potato were 81.4 and 79.6, respectively and was not significantly different. Three starch extraction systems 1, 2 and 3 were tested using the "Hoang long" and "Tu nhien" sweet potato varieties. The effects of sweet potato variety and extraction system on processing parameters such as dry matter, conversion rate, extraction efficiency, specific power consumption, sweet potato residue, starch color etc., were studied. A 27 to 29 minutes filtering time and 120 to 125 liters of water use were found to be optimal for the filtering machine using starch extraction system 2. A rpm of 1600 to 1700 and water use of 2.6 liters per kg of ground fresh root, were found to be optimal working conditions for the combined grating and filtering machine in system 3. The Financial Rates of Return (FRR) was found to be 31.43, 31.45 and 32.72% for system 1, system 2 and system 3, respectively, and were higher than the minimum acceptance FRR of 26%. The sensitivity of different processing parameters to the FRR for each system were also determined. The use of different sweet potato starch extraction systems in different ecological zones of Vietnam are also presented.
A thesis submitted in partial fulfillment of the requirement for the Degree of Master Engineering, School of Environment, Resources & Development
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Sweet potato products -- Vietnam